The Determinants of Macroeconomic Conditions and Bank-Specific Factors on the Growth of Islamic Banking in Indonesia during the 2018–2023 Period - Zaenuri, Muhamad Havis; Tamara, Destian Arshad Darulmalshah; Ridha, Noorsyah Adi Noer; Syaiful, Muhammad (Journal of Applied Islamic Economics and Finance, 2025)
This research aims to analyze the impact of macroeconomics conditions and bank-spesific factors on the asset growth of islamic commercial banks in Indonesia in Indonesia during the period 2018-2023. The macoeconomic conditions are proxied by GDP, Inflastion, ad BI-Rate, while the bank spesific factors are proxied by the FDR, ROA and Third-Party Funds. The data analysis is quantitative descriptive analysis, and the research method used is panel data regression. The results indicate that the FDR and DPK variables have a positive and significant impact on the asset growth of Islamic Commercial Banks in Indonesia. Meanwhile, the BI-Rate and GDP variables have a positive but insignificant effect, and the ROA and inflation variables have a negative but insignificant effect. The Adjusted R² value of 0.0786 shows that the independent variables used in this study explain 7.86 percent of the variation in the total asset growth of Islamic Commercial Banks in Indonesia, while the remaining 92.14 percent is explained by other factors outside the model.